Better (RED) than dead: 'brand aid', celebrities and the new frontier of development assistance - Lisa Ann Richey; Stefano Ponte (Danish Institute for International Studies (DIIS), 2006)
Bono's launch of Product (RED)™ at Davos in 2006 marks the opening of a new frontier for development aid. The advent of `Brand Aid' explicitly linked to commerce, not philanthropy, reconfigures the modalities of international development assistance. American Express, Gap, Converse and Armani represent the faces of ethical intervention in the world, as customers are encouraged to do good by dressing well. Consumption, trade and aid wed dying Africans with designer goods, as a new social contract is created to generate a sustainable flow of money to support The Global Fund to Fight AIDS, Tuberculosis and Malaria. Aid celebrities – the bard, the teacher and the healer – guarantee the `cool quotient,' the management and the target of this new modality. Bono is the rock-star who led his fans to believe that they could solve Africa's problems of AIDS and poverty. Jeffrey Sachs is the recently-radicalized economist who masterminded The Global Fund. And Paul Farmer is the physician who convinced the world that treatment of AIDS was possible in even the poorest communities. The consumer's signification of status through designer RED products does not represent the exploitation of the most downtrodden – it actually helps them. `Brand Aid' creates a world where it is possible to have as much as you want without depriving anyone else. Promoted as new leftist development chic, compassionate consumption effectively de-links the relations of capitalist production from AIDS and poverty.
Keywords: 330; AIDS; Gesundheitsvorsorge; Mode; Handelsmarke; Afrika